Experimental study on the effects of rainwater infiltration and cyclic loading on unsaturated silica sand - P.H.H. Giang; T. Uchimura; L.G. Lam; W. Haegeman (International Association of Lowland Technology, 2016)
This paper presents the result of cyclic loading tests followed by water infiltration on unsaturated sandy samples to study possible slope failures in earthquake areas. The cyclic tri-axial tests and dynamic measurements were carried out on Edosaki sand, silica sand taken from a natural slope in Chiba prefecture in Japan. The specimens were first consolidated in anisotropic condition with a principal stress ratio (K = 2), and then cyclically loaded under un-drained conditions. After cyclic loading, water infiltration was applied to the specimens until failure after different periods of waiting time. During the tests, the elastic wave velocities were continuously measured. Test results clearly show the variation of stiffness during cyclic loading and infiltration attributed to changes in relative density. Test results also confirm that there is a possible threshold value for the cyclic amplitude that causes a rearrangement of the soil skeleton and gives rise to higher failure resistance during water infiltration after reconsolidation. In short, it is very useful to monitor the stiffness and pore water pressure in a slope after an earthquake in areas with high and frequent rainfall.